A single-case experimental evaluation of a new group-based intervention to enhance adjustment to life with acquired brain injury: VaLiANT (valued living after neurological trauma). Issue 8 (14th September 2022) - Sathananthan, Nick; Dimech-Betancourt, Bleydy; Morris, Eric; Vicendese, Don; Knox, Lucy; Gillanders, David; Das Nair, Roshan; Wong, Dana
ABSTRACT: Adjustment to life with acquired brain injury (ABI) requires self-identity and behaviour to be updated, incorporating injury-related changes. Identifying and enabling new values-consistent behaviours could facilitate this process. We evaluated the feasibility, acceptability, and preliminary efficacy of VaLiANT, a new group intervention that aims to enhance "valued living" following ABI. We used a non-concurrent multiple baseline single-case experimental design (SCED) with an 8-week follow-up phase and randomization to multiple baseline lengths (5–7 weeks). Eight participants (50% women, aged 26–65; 4 Stroke, 3 Traumatic Brain Injury, 1 Epilepsy) attended eight group sessions with assessments before, during, and after the group. Target behaviour was valued living, assessed weekly by the Valued Living Questionnaire. Secondary outcomes included measures of wellbeing, mood, psychological acceptance, self-efficacy regarding ABI consequences, cognitive complaints, and intervention acceptability. Target behaviour was analysed through visual and statistical analysis while secondary outcome data were analysed via reliable change indices and descriptive statistics. Target behaviour data displayed no convincing patterns of improvement. Reliable improvements were found for most participants on secondary outcomes, particularly subjective wellbeing and anxiety. Intervention delivery was feasible with high acceptability ratings. Further investigation of VaLiANT is warranted, based on the feasibility and acceptability of intervention delivery and signals of efficacy identified across adjustment-related secondary outcomes.